The Political Culture of the Cigugur Society, Indonesia - Suhadi,; Casmana, Asep Rudi; Syafrudin, Iqbal (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to look at the political culture in the Cigugur region, Kuningan, West Java. Judging from the theory to be used, political culture is divided into three namely parochial political culture, subjects and participants. Seeing the complexity of society in the West Java region, researchers are very interested in the conception of political culture inherent in the brass community, so that this can provide scientific treasures. The method that will be used in this research is descriptive qualitative, where the research instrument is through a semi- structured interview. This method makes it easy for researchers to be able to communicate directly to the participants informally, so that participants hope to be able to provide their political views to researchers. The sampling technique that will be used is snowball sampling. This technique also makes it easier for researchers to be able to find out who can be interviewed through previous participants. The expected benefit or result of this research is a description of the political culture of the Cigugur community as a whole, so that it can make a recommendation or suggestion for the government so that it can be used as a reference in the future. The results show that the people of Cigugur, Kuningan, West Java are included in the participant community. This was concluded because they had been actively involved in regional head elections and general elections.